In repeat: scars, structures and surfaces - Miller, Carrie, author; Lundberg, Thomas, advisor; Bates, Haley, committee member; Fahey, Patrick, committee member; Kissell, Kevin, committee member (Colorado State University. Libraries, 2018)
This body of work investigates the veiling and revealing of physical and emotional scars. A link is made between these kinds of scarring by observing the structured space that the body provides for the psyche. While equating the body with a container, these artworks animate the cyclical nature of re-growth and regression through a breadth of forms. In my studio practice, I explore cloth as a gendered, sexually charged space. Through their relationships to the body and their cultural associations, the textile materials in my work probe the boundaries of body and psyche, public and private, and decorative and abject. How can cloth capture subtle and metaphorical relationships in the healing and scarring process of the body and the psyche? Cloth, as the ubiquitous second skin, provides access points for the viewer. In a global society, the symbolism of cloth can often be contradictory. Throughout history, women's dress has included garments that act as veils. Simultaneously, veils embody protection, modesty, seduction and subtle combinations of all three. In many of these works, qualities of transparency are emphasized to explore what is exposed and what is hidden in the body and the psyche. This body of work is comprised of four handwoven pieces and two painted textile pieces. Omissions (Fig. 1), Old Growths (Fig. 2) Bandage (Fig. 3) and Optional Endings 1-5 (Fig. 4) are handwoven while My Body at Home (Fig. 5) and My Body at Home II (Fig. 6) are soft wall sculptures.
Keywords: scars; textiles; weaving; skin; fibers; veiling